Predictors of effectiveness of multidisciplinary rehabilitation treatment on motor dysfunction in multiple sclerosis. (June 2014) - Liberatore, G; Clarelli, F; Nuara, A; Ungaro, D; Gatti, R; Rovaris, M; Martinelli, V; Comola, M; Comi, G; Rossi, P; Martinelli-Boneschi, F
Objectives: To identify clinical predictors of effectiveness of a motor rehabilitation treatment in a cohort of multiple sclerosis (MS) patients. Materials and methods: We analysed 212 consecutive patients who underwent a short-term (3–7 weeks) intensive (two hours per day, five days per week), individualised, goal-oriented inpatient rehabilitation program. Activity limitation and impairment were measured on admission and discharge of the rehabilitation trial using the motor sub-items of the Functional Independence Measure (mFIM) and the Expanded Disability Status Scale (EDSS) score. Multivariate logistic regression models have been tested to evaluate the role of clinical baseline features on rehabilitation effectiveness. Results: According to pre-defined outcome measures, 75.1% of MS patients improved in either activity limitation (≥5 points delta mFIM) or impairment (≥1.0 delta EDSS score if baseline EDSS was ≤5.5, or ≥0.5 if baseline EDSS was >5.5), and 35.4% of MS patients improved in both outcomes. A relapsing-remitting course of disease, a more severe baseline impairment and activity limitation level, a shorter disease duration and a less severe balance dysfunction were predictive of the effectiveness of rehabilitation. Discussion: These data confirm that an intensive inpatient rehabilitation program is able to produce a short-term relevant improvement on clinical and functional outcome measures and suggest some clinical features which can be considered as potential predictors of the outcome of rehabilitative intervention.